Penggunaan Perangkat Lunak Energy2D dalam Mempelajari Konduktivitas Panas Pada Plastik - Budiana Budiana; Rifaldi Dwi Priana; Xena Mutiara Sinurat; Canderif Amsal Oloan Silaban (JURNAL INTEGRASI, 2021)
Plastic is one type of material that has certain characteristics against heat. One of the characteristics of plastics that can be studied is thermal conductivity. Thermal conductivity is the ability of a material to conduct heat within a certain period of time and at a certain thickness. The thermal conductivity of plastics can be studied using Energy2D. The types of plastics used in this study consisted of polypropylene, polystyrene, HDPE, LDPE and PET while the thickness used varied from 1 cm to 9 cm. Based on the simulation, the type of polypropylene plastic has the lowest curve when compared to all the materials used. The time it takes for the outside (source) temperature to equal the room temperature after passing through the polypropylene is (> 40 hours). Apart from that, the time it takes for the outside temperature to be equal to the indoor temperature will be longer if the polypropylene used is getting thicker. This can be seen for the thickness of polypropylene with a thickness of 9 cm which takes time (> 60 hours).